Bidding strategy for a prosumer aggregator with stochastic renewable energy production in energy and reserve markets. (May 2022) - Sun, Guoqiang; Shen, Sichen; Chen, Sheng; Zhou, Yizhou; Wei, Zhinong
Abstract: A growing body of electricity consumers with renewable energy and demand response resources have become active prosumers who can both produce and consume energy. However, the small size of most prosumers forbids their direct participation in electricity markets. This study addresses this issue by proposing a bidding strategy for the prosumer aggregator based on a bi-level model to enable multiple prosumers to participate in day-ahead energy and reserve markets as a single entity. Here, the prosumer aggregator profit and social welfare are maximized in the upper-level and lower-level models, respectively, where the heating, ventilation, and air-conditioning system loads, residential loads, energy outputs associated with photovoltaic power generators, and energy storage systems are included. The Karush–Kuhn–Tucker condition and strong duality equalities are used to transform the proposed bi-level model into a single-level model. The effectiveness and economy of the proposed approach are demonstrated based on the numerical results obtained for a realistic test system. Highlights: We develop a bi-level model for prosumers in energy and reserve markets. The uncertainty of renewables is accommodated by the prosumer aggregator. The economic value of the proposed stochastic model is quantified. The flexibility provided by a prosumer aggregator is exploited.